Electrical impedance tomography in children with community acquired pneumonia: preliminary data. (September 2017) - Mazzoni, Marta B.; Perri, Alessandra; Plebani, Anna M.; Ferrari, Silvia; Amelio, Giacomo; Rocchi, Alessia; Consonni, Dario; Milani, Gregorio P.; Fossali, Emilio F.
Abstract: Background: Electrical impedance tomography (EIT) is a noninvasive pulmonary function test that provides spatial and temporal information of changes in regional lung ventilation. We aimed to assess the feasibility of EIT as a supplementary tool in the evaluation of community acquired pneumonia in children. Furthermore, we performed a prospective evaluation of regional lung ventilation changes during a six-month follow-up period. Methods: We enrolled otherwise healthy children aged 2–15 years with radiological diagnosis of community acquired pneumonia on admission at pediatric emergency department. Chest EIT was performed at enrollment, at three and six-months from baseline. Results: Nineteen children were enrolled. A significant agreement between EIT and chest radiography in identifying the affected lung (left or right) was observed (Cohen K statistic = 0.73, 95% CI 0.5–0.98). Ventilation improvement was documented at three-month follow-up, but a full recovery only at six months. Conclusion: EIT reliably provides additional information on lung ventilation disorders due to CAP in children. It further allows bedside, real time and radiation free monitoring of lung functional recovery. Future studies are needed to expand the generalizability of this method and evaluate effectiveness on clinical practice. Highlights: Electrical impedance tomography (EIT) is a promising tool for lung evaluation in community acquired pneumonia (CAP). EIT might be also useful for monitoring ventilation improvement during CAP follow-up. Further studies are necessary to investigate the potential clinical role of EIT in children with CAP.